Current recruitment process in Panasonic Semiconductor Discrete Devices (M) Sdn Bhd - Mokhtar, Nur Fatina (2011)
The introduction of this research paper includes background of the company, issues, objective and significant of the study. The main topic in this paper is recruitment trend in Panasonic Semiconductor Discrete Devices (M) Sdn. Bhd. (PSCDDM). Recruitment is defined as any activity carried on by the organization with the primary purpose of identifying and attracting potential employees. (Raymond A. Noe, John H. Hollenbeck, Barry Gerhart, Patrick M. Wright (2009). The recruitment process is important in the organization because it will affect the performance of the organization and thus the financial performance itself. Different organization has different strategies of recruitment process and in the case of PSCDDM, the recruitment process will be discover later in chapter 2. Other than that, recruitment also plays an important role to the human resource management because they need to plan and forecast for the manpower required to suit the specific position. The process of hiring begins with human resource planning (HRP) which helps to determine the number and type of people on organization needs. Effective human resource planning helps in determining the gaps present in the existing manpower of the organization. It also helps in determining the number of employees to be recruited and what qualification they must possess. Job analysis and job design enables to specify the task and duties of hobs and qualification expected from prospective job HRP, job analysis, job design helps to identify the kind of people required in an organization and hence hiring. It should be noted that hiring is an ongoing process and not confined to formative stages of an organization. In this research paper, the case study on recruitment concept, recruitment process and recruitment method will be discover in PSCDDM and how they implement it.